2010
DOI: 10.1093/treephys/tpq078
|View full text |Cite
|
Sign up to set email alerts
|

Organic fertilization leads to increased peach root production and lifespan

Abstract: We evaluated the effects of mineral and organic fertilizers on peach root dynamics in the growing season from 2003 to 2006 in a nectarine (Prunus persica L.) orchard, planted in 2001 and located in the Po valley, northeastern Italy. Very few studies have conducted long-term investigations of root dynamics of fruit crops. Our main objective was to determine whether organic fertilizers affect root dynamics differently than mineral fertilizers. The experiment was a completely randomized block design with four rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 41 publications
5
41
1
1
Order By: Relevance
“…This is consistent with greater root production and lifespan induced by compost and mulching as compared to mineral fertilizer [40]. In addition, mineral fertilizer induces high nitrate ( 3 NO − ) pulses, which could easily be leached as a result of its high mobility in the soil, coupled with the heavy rainfall condition of the study area.…”
Section: Impact Of Isfm On Tomato Performancesupporting
confidence: 81%
“…This is consistent with greater root production and lifespan induced by compost and mulching as compared to mineral fertilizer [40]. In addition, mineral fertilizer induces high nitrate ( 3 NO − ) pulses, which could easily be leached as a result of its high mobility in the soil, coupled with the heavy rainfall condition of the study area.…”
Section: Impact Of Isfm On Tomato Performancesupporting
confidence: 81%
“…Consequently, the yield per plant and per hectare in 2008 and 2009 increased quadratically (Table 4). This result potentially occurred because the added compost was mineralized by microorganisms and the nutrients within the compost were released (Baldi, Toselli, Eissenstat, & Marangoni, 2010b;Ramos et al, 2011), which would increase the TOC content, mineral N, available P, and the exchangeable K, Ca, and Mg contents in the soil quadratically (unpublished data) as the addition of compost increased at 72 L compost per plant -1 . Some studies showed that the application of organic compost in the soil improved the soil physical attributes by increasing the soil porosity and reducing the soil density (Erhart, Feichtinger, & Hartl, 2007;Melo et al, 2012).…”
Section: Nutritional Status and Fruit Yieldmentioning
confidence: 99%
“…C treatment compared to the control treatment observed in the first year may suggest otherwise. Nonetheless, the effect of compost on growth and crop yield in fruit trees has been shown to vary from neutral to positive effects, depending on the nature, and rate of compost application (Baldi et al 2010;van Schoor et al 2012). The positive effect of biochar treatment on growth responses was not evident until year 3 suggesting that the full effects of biochar treatment on perennial fruit tree responses may not be realised by short timescale studies.…”
Section: Tree Growth and Crop Yieldmentioning
confidence: 99%